2013
DOI: 10.5664/jcsm.2414
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Supplementary Internet Based Education Program Improves Sleep Literacy in College Psychology Students

Abstract: pertaining to healthy sleep. 7 Unfortunately, the amount of time devoted to information about sleep in these courses may be as little as one hour of lecture.In the past 10 years, use of the Internet among all segments of the population has been increasing rapidly. Educational uses have been growing and online college courses and degree programs are offered by many prestigious institutions. Educational Introduction: Knowledge regarding the importance of sleep in health and performance and good sleep hygiene pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
27
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 15 publications
4
27
0
3
Order By: Relevance
“…Thus, the results are consistent with our previous study demonstrating a positive impact on sleep knowledge and behavior in a group of undergraduates enrolled in an introductory psychology course using an internet-based educational module (7). In addition, Kloss et al reported improvements in sleep hygiene knowledge and sleep quality four weeks after an in-person sleep educational intervention (12).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Thus, the results are consistent with our previous study demonstrating a positive impact on sleep knowledge and behavior in a group of undergraduates enrolled in an introductory psychology course using an internet-based educational module (7). In addition, Kloss et al reported improvements in sleep hygiene knowledge and sleep quality four weeks after an in-person sleep educational intervention (12).…”
Section: Discussionsupporting
confidence: 81%
“…Thus, a sleep educational program delivered over the internet has the potential to reach large numbers of students. In a recent study, we demonstrated that an internet-based sleep learning module administered as component to an introductory college psychology course resulted in an improvement in sleep knowledge and changes in sleep habits (7). In an effort to provide a more comprehensive sleep educational intervention, we have developed an interactive internet-based sleep course, "Sleep 101."…”
Section: Introductionmentioning
confidence: 99%
“…Compared to students who were not enrolled in the course, the researchers found marginal effects for sleep quality and nap time, and emphasized the need for greater attention to insufficient sleep and daytime sleepiness. Quan and colleagues 30 found that an Internet supplement on sleep (delivered to undergraduates as part of their Introduction to Psychology course) resulted in small increases in sleep knowledge, more consistent wake times, and active attempts to increase their total sleep times relative to those in the control group. Trockel and colleagues 28 found that an 8-session, emaildelivered, cognitive-behavioral program yielded decreases in depressive symptoms and enhanced sleep quality among poor sleepers.…”
Section: Introductionmentioning
confidence: 97%
“…[27][28][29][30][31] Brown and colleagues' 27 one meeting Sleep Treatment and Education Program (STEPS) demonstrated improvements after 6 weeks in sleep hygiene practices and sleep quality among college students, compared to a control group. Their program was comprised of a 30-minute educational presentation delivered in an introductory psychology course and focused on sleep hygiene education procedures.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21] Apart from institutional changes, effective educational interventions can increase sleep duration and improve sleep habits from preschool to college students. [22][23][24] Now is the time to translate this research into implementation. Schools, including colleges and universities, need sleep-friendly policies and start times, based on the best practices for our students.…”
mentioning
confidence: 98%